Teksty modlitw eucharystycznych w świetle najnowszych zasad pisowni słownictwa religijnego - Michał Machura (Polonia Sacra)
The article discusses the texts of eucharistic prayers from the perspective of recent religious vocabulary spelling rules approved by the Polish Language Council in 2010 and published in 2011. The article presents the characteristics of the most common linguistic errors that appear in the titles and texts of prayers. Both of them concern misspellings and punctuation errors. The first group of aberrations concern too frequent use of the capital letter and the wrong spelling of periphrases. The Author admit that although the writers may use capital letter by emotional reasons, nevertheless, they should use this consciously and responsibly as to not to obliterate the differences of meaning between words.